Outcomes of Liver Transplant Recipients With Acute-on-Chronic Liver Failure Based on EASL-CLIF Consortium Definition: A Single-center Study. Issue 4 (April 2020) - Agbim, Uchenna; Sharma, Anuj; Maliakkal, Benedict; Karri, Saradasri; Yazawa, Masahiko; Goldkamp, William; Podila, Pradeep S.B.; Vanatta, Jason M.; Gonzalez, Humberto; Molnar, Miklos Z.; Nair, Satheesh P.; Eason, James D.; et al.
Abstract : Background: The impact of acute-on-chronic liver failure (ACLF) defined by European Association for the Study of the Liver-Chronic Liver Failure in liver transplant (LT) recipients has not been well characterized. The aim of the study was to assess early posttransplant morbidity and survival of ACLF patients. Methods: Eight hundred twenty-five consecutive LT patients (04/2006–03/2013) were included in a retrospective analysis. Of the 690 evaluable patients, 589 had no ACLF, and the remaining 101 were grouped into ACLF Grades 1–3 (ACLF Grade 1: 50 [49.5%], ACLF Grade 2: 32 [31.7%], and ACLF Grade 3: 19 [18.8%]). Results: LT recipients transplanted in the context of ACLF had significantly increased serum creatinine (2.27 ± 1.16 versus 0.98 ± 0.32; P < 0.0001), and inferior 1-year graft (90% versus 78%; P < 0.0001) and patient survival (92% versus 82%; P = 0.0004) by Kaplan-Meier survival analysis; graft and patient survival correlated negatively with increasing severity of ACLF. One-year graft and patient survival were lower in those with high ACLF (Grade 2 and 3) irrespective of Model for End-Stage Liver Disease compared with other groups. The ACLF group had longer intensive care unit stays (10.6 ± 19.5 versus 4.2 ± 9; P < 0.0001), hospital stays (20.9 ± 25.9 versus 11.7 ± 11.4; P < 0.0001), and increased surgical re-exploration (26.7 % versus 14.6%, P = 0.002). Conclusions: Patients with ACLF undergoing LT have significantly higher resource utilization, inferior graft survival and patient survival, and renal dysfunction at 1 year. The combination of ACLF and Model for End-Stage Liver Disease can be considered when determining the suitability for potential transplantation. Abstract : Supplemental Digital Content is available in the text.